O gênero Stereocaulon (Schreb.) Hoffm. (Ascomycota liquenizados, Stereocaulaceae) em altas montanhas e altas latitudes na América do Sul e na Antártica - Jean Marc Edson Torres Pineda (2023)
Stereocaulon (Schreb) Hoffm. is a tripartite genus of lichens: the thallus results from the symbiotic association between an Ascomycota fungus, a green algae and a cyanobacteria. There are around 150 species accepted worldwide, and their distribution is cosmopolitan, although most species have a certain preference for regions of high altitudes and latitudes. The dimorphic thallus of Stereocaulon is easily recognizable in the field, but species identification is not an easy task. The high intraspecific phenotypic variability is little discussed in studies and can lead to erroneous identifications. In Antarctica and South America, the studies are scarce; most of the work evaluating the taxonomy and systematics of the genus is based mainly on specimens from Europe, North America and Asia. With the aim of contributing to the understanding of the taxonomy and systematics of Stereocaulon from specimens from the southern hemisphere, in this study, morphological, chemical and molecular analyzes were carried out on species found in Tierra del Fuego and Patagonia (Argentina and Chile), in Antarctica, in the campos de altitude of Brazil and the Andean Paramos of Colombia. In total, 920 Stereocaulon specimens were examined. For each species we present information about their morphology, anatomy and chemical composition. We also generated 332 new sequences of the nuclear DNA internal transcribed spacer (nuITS) and 97 new sequences of the gene encoding the protein beta tubulin (β-tubulin) for mycobionts, and five new sequences of the gene encoding the actin I protein (ACT1) and ten of the region 16S ribosomal DNA (16S rDNA) for the chlorobiont and cyanobiont of S. alpinum, respectively, totaling 444 new sequences generated. Were identified 22 species of Stereocaulon, seven for the high latitudes of southern South America in Argentina and Chile, three for Antarctica, four for the campos de altitude of Brazil and 17 for the Andean Paramos of Colombia. Stereocaulon alpinum was characterized, described and confirmed as a bipolar species. For the campos de altitude in Brazil, S. vesuvianum represents a new record for the Brazilian territory. In this study, we realized that in some cases, the descriptions found in the literature do not cover or reflect the morphological variability found in the species. Therefore, meticulous and detailed descriptions of the morphology, anatomy and chemistry of the species are of great importance for the circumscription of each species, which is reflected and confirmed in molecular analyses. Molecular tools are essential to carry out integrative analyzes that allow a better understanding of the systematics of the genus. Key words: dimorphic thallus, phylogeny, symbioses, taxonomy.